An atlas of agendas : mapping the power, mapping the commons - Holmes, Brian; Lomme, Freek; Onomatopee (Gallery); Bureau d'Études (Artists' group) (Eindhoven : Onomatopee, 2015)
Together, Paris-based artists Léonore Bonaccini and Xavier Fourt make up the artist duo Bureau dþÉtudes. For the past several years, this French group has been producing cartographies of contemporary political, social and economic systems which allow people to empower and reposition themselves. Revealing what normally remains invisible, often in the shape of large-sized banners, and contextualizing apparently separate elements within another framework, these visualizations of people’s interests and relations re-symbolize and actualize an order concealed and unknown.
Includes index.
A plastic magnifying lense located in mounted plastic pocket, inside front cover. One folded sheet attached to inside back cover.
"Released in the aftermath of the exhibition at Onomatopee project space Eindhoven, October 2013"--Colophon.
Limited edition of 1000 copies.
boek
Keywords: Bureau d'Études (Artists' group); Art and social action -- Exhibitions